Junior High School Need For Students’ Workbook Based on Local Wisdom in Merdeka Curriculum - Kurniawan, Nasri; Yuliana, Yohanes Gatot Sutapa; Regina, Regina (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to explore the need for students' workbooks based on local wisdom in the Merdeka Curriculum for junior high school students, particularly at SMPN 3 Air Besar. The study is motivated by the importance of local wisdom in shaping students' character and identity, as well as the need for appropriate teaching materials that can support the implementation of the Merdeka Curriculum. This study employed a survey research design to elicit information. To identify the students' needs, data was collected through questionnaires, interviews, and direct observations. The interviews were conducted with students, English teachers, and villagers to gather in-depth information about the students' needs in the materials design. The study proposes various positions for EFL teachers to perform, including visionaries, cultural mediators on a local level, intercultural educators, and role model practitioners. It offers strategies for EFL teachers to include local cultural elements into their classroom instruction, such as establishing a local culturally responsive pedagogy, cultural sensitivity and awareness, and leveraging technology and information to support teaching. Incorporating local culture into EFL teaching can benefit students by raising cultural awareness, developing cultural literacy, building intercultural competence, enhancing language learning experiences, and acquiring skills in eliciting meaning. By using a workbook that takes into account the specific requirements of the students, teachers can better address their learning needs and create a more effective and engaging learning environment. It is recommended that English language teachers utilize the workbook that is based on local wisdom, as it aligns with the Indonesian National Educational System and the current Merdeka Curriculum, which emphasizes the relation between teaching English and the learners' closest environment for meaningful language use. Overall, the study focuses on exploring the need for a supplementary workbook that integrates local wisdom and culture into English language teaching, aiming to enhance students' language proficiency and cross-cultural communication skills.